2021
DOI: 10.1182/blood-2021-151490
|View full text |Cite
|
Sign up to set email alerts
|

PHF6 Positively Regulates Transcription of Myeloid Differentiation Genes By Binding at Enhancer Regions

Abstract: Acute myeloid leukemia (AML) is a hematopoietic malignancy characterized by uncontrolled division, and differentiation arrest, of hematopoietic stem cells (HSCs) and myeloid progenitors. AML is a genetically heterogeneous disease, with mutations in genes belonging to multiple functional groups. Of these, chromatin regulators and transcriptional factors (TFs) are an important functional group to study because of a lack of targeted AML therapies against these factors. PHD Finger Protein 6 (PHF6) is one such chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…As a consequence, this cooperation would induce differentiation to myeloid lineage and suppress differentiation to lymphoid lineage. This was in line with a previous report demonstrating that PHF6 co-localizes with RUNX1 in promoter regions 19 . The chromatin-binding capacity of PHF6 is essential for differentiation function in AML, as shown in B-ALL 9 .…”
Section: Discussionsupporting
confidence: 93%
“…As a consequence, this cooperation would induce differentiation to myeloid lineage and suppress differentiation to lymphoid lineage. This was in line with a previous report demonstrating that PHF6 co-localizes with RUNX1 in promoter regions 19 . The chromatin-binding capacity of PHF6 is essential for differentiation function in AML, as shown in B-ALL 9 .…”
Section: Discussionsupporting
confidence: 93%
“…However, whether PHF6 regulation of the genome could also be epigenetically encoded in the context of BFLS pathogenesis remains a subject for future studies. In investigating the pattern of PHF6 binding to the genome, we found enrichment in the 5’ UTR and TSS consistent with previous studies in B-cell leukemia where PHF6 was shown to bind to the TSS, the 5’ UTR (Soto-Feliciano et al, 2017 ), and enhancer regions in a model of acute myeloid leukemia (AML) (Pawar et al, 2021 ). Notably, consistent with our findings in stem cell regulation, other groups have also reported a role for PHF6 in cell differentiation (Pawar et al, 2021 ) and lineage specification (Soto-Feliciano et al, 2017 ) in leukemia myeloid cell models.…”
Section: Discussionsupporting
confidence: 89%